Steroid metabolomic signature of liver disease in nonsyndromic childhood obesity. Issue 6 (June 2019) - Gawlik, Aneta; Shmoish, Michael; Hartmann, Michaela F; Wudy, Stefan A; Olczak, Zbigniew; Gruszczynska, Katarzyna; Hochberg, Ze'ev
Abstract : Objective: Analysis of steroids by gas chromatography-mass spectrometry (GC-MS) defines a subject's steroidal fingerprint. Here, we compare the steroidal fingerprints of obese children with or without liver disease to identify the 'steroid metabolomic signature' of childhood nonalcoholic fatty liver disease. Methods: Urinary samples of 85 children aged 8.5–18.0 years with BMI >97% were quantified for 31 steroid metabolites by GC-MS. The fingerprints of 21 children with liver disease (L1) as assessed by sonographic steatosis (L1 L ), elevated alanine aminotransferases (L1 A ) or both (L1 AL ), were compared to 64 children without markers of liver disease (L0). The steroidal signature of the liver disease was generated as the difference in profiles of L1 against L0 groups. Results: L1 comparing to L0 presented higher fasting triglycerides ( P  = 0.004), insulin ( P  = 0.002), INS/GLU ( P  = 0.003), HOMA-IR ( P  = 0.002), GGTP ( P  = 0.006), AST/SGOT ( P  = 0.002), postprandial glucose ( P  = 0.001) and insulin ( P  = 0.011). L1 AL showed highest level of T-cholesterol and triglycerides ( P  = 0.029; P  = 0.044). Fasting insulin, postprandial glucose, INS/GLU and HOMA-IR were highest in L1 L and L1 AL ( P  = 0.001; P  = 0.017; P  = 0.001; P  = 0.001). The liver disease steroidal signature was marked by lower DHEA and its metabolites, higher glucocorticoids (mostly tetrahydrocortisone) and lower mineralocorticoid metabolites than L0. L1 patients showed higher 5α-reductase and 21-hydroxylase activity (the highest in L1 A and L1 AL ) and lower activity of 11βHSD1 than L0 ( P  = 0.041, P  = 0.009, P  = 0.019). Conclusions: The 'steroid metabolomic signature' of liver disease in childhood obesity provides a new approach to the diagnosis and further understanding of its metabolic consequences. It reflects the derangements of steroid metabolism in NAFLD that includes enhanced glucocorticoids and deranged androgens and mineralocorticoids.